Intellectual property assessment: development of information and methodological support in conditions of limited information - Momot, Tetyana; Karpushenko , Maria; Prilipko , Serhiy; Mushchynska , Natalia; Momot , Darina (Eastern-European Journal of Enterprise Technologies, 2021)
Assessment of intellectual property is an important process of commercialization of scientific and technical developments of enterprises of all forms of ownership. This is carried out to determine the value of intellectual property objects (IPO) in connection with the transfer of ownership (purchase, sale) to the corresponding object, the conclusion of a license agreement for the IPO use, accounting for IPO in accounting, contributed to the authorized capital, etc. Under such conditions, the problem of IPO underestimating significantly reduces the efficiency and effectiveness of enterprises. At the same time, the uniqueness of many types of intellectual assets and the impossibility of their visual assessment determine the expediency of systematizing methodological approaches to assessing the value of intellectual property assets to ensure an objective assessment of the value of intellectual property. This will help increase the profitability and business value of the enterprise. The aim of research is to develop theoretical and methodological provisions and substantiate practical recommendations for improving information and methodological support for assessing the value of intangible assets, taking into account the requirements of regulatory documents and the availability of the necessary information. Based on the results of the study, methodological approaches to determining the value of intangible assets are systematized. According to the financial statements, the value of intangible assets of the leading enterprises of Ukraine and their share in the total value of assets were analyzed. The features of the assessment of intangible assets in accordance with accounting standards have been determined, a methodological approach to the assessment of the value of intellectual property has been developed, it allows to reasonably choose a method for assessing IPO based on the analysis of available information. It is proved that the lack of objective information on the value of IPO significantly reduces the value of assets of Ukrainian enterprises in comparison with the leading companies in the world, reduces their investment attractiveness and does not contribute to economic development